Programa de intervención para mejorar los componentes de la inteligencia emocional durante la pandemia en estudiantes de psicología de la Universidad Antonio Nariño (2021)
The general objective of this research paper is to design an intervention program to improve the emotional intelligence components of psychology students at the Antonio Nariño University, an empirical-analytical approach, with descriptive scope, was implemented methodologically to obtain the necessary data by applying the Barón Emotional Intelligence Inventory in a population of 20 people, taking into account the inclusion criteria, these should have been between the age range of 16 to 21 years, in addition to being students of the Antonio Nariño University of the psychology program, after applying this inventory which consists of 133 questions that evaluate different components of emotional intelligence and taking